2017
DOI: 10.1149/2.0991713jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Coating on Gas Evolution and Impedance Growth at Li[NixMnyCo1-x-y]O2Positive Electrodes in Li-Ion Cells

Abstract: The effects of surface coatings on Li[Ni x Mn y Co z ]O 2 (NMC, x+y+z = 1, x:y:z = 4:4:2 (NMC442), x:y:z = 5:3:2 (NMC532), x:y:z = 6:2:2 (NMC622)) electrodes in pouch cells and pouch bags, containing electrolyte with a certain additive blend, were systematically studied. Ex-situ gas measurements, gas chromatography coupled with a thermal conductivity detector and electrochemical impedance spectra were used to study the reactions that occurred. The results obtained from pouch bag experiments at elevated tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…In addition to the high frequency semicircle observed after formation cycles, a second semicircle appeared at lower frequency for all cathodes after aging cycles, which could be attributed to the development of charge-transfer impedance of slower process. 31,32 As summarized in Figure S6b, all cycled cathodes had significantly higher impedance after aging cycles. The strong cathode impedance growth may come from side reactions that occur at the cathode surface during cycling 33,34 and the formation of surface reconstruction layers.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to the high frequency semicircle observed after formation cycles, a second semicircle appeared at lower frequency for all cathodes after aging cycles, which could be attributed to the development of charge-transfer impedance of slower process. 31,32 As summarized in Figure S6b, all cycled cathodes had significantly higher impedance after aging cycles. The strong cathode impedance growth may come from side reactions that occur at the cathode surface during cycling 33,34 and the formation of surface reconstruction layers.…”
Section: Resultsmentioning
confidence: 94%
“…For example, the degradation of NMC811 cells was studied by using different electrolyte additives including VC and PES211 to suppress side reactions and it was revealed that NMC442/graphite cells and NMC111/graphite cells showed better performances with PES211, whereas NMC811/graphite cells aged slower with VC (with slower capacity fading and impedance growth) [79]. Here, PES was also reported to be a viable additive for the suppression of gas evolution [91] and impedance growth during cycling to higher voltages (above 4.3 V), and rocksalt surface layers formed with the use of VC but not with PES211, concluding that electrolyte additives can significantly affect the rate of parasitic reactions and that parasitic reactions were the main reason for capacity fading [7,92].…”
Section: Parasitic Reaction: Effects Of Nimentioning
confidence: 99%
“…Li-free coatings on the outer surface of NMC cathodes have been extensively investigated due to a unique advantage over doping in which the valence of transition metal ions remains unaffected and so does the theoretical capacity. Here, materials used for Li-free coating include transition metal phosphates [187], metal oxides [99,188,189], fluorides [143,190], silicon oxide [91,100] and organic coating layers [138,191] in which the general concept is to prevent cathode surfaces containing highly reactive Ni 4+ from contacting the electrolyte and therefore to reduce side reactions. Here, coating layer thicknesses are usually between 5 and 40 nm and similar to doping, XRD measurements usually do not show new characteristic peaks and instead, existing peak widths/positions may change slightly.…”
Section: Li-free Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The BE peaks ( Figure 4b) at 464.05 and 466.88 eV could be assigned to Ru 3 + and Ru 4 + , respectively. [22] And the major existing form of Ru in Ru/CB is Ru 3 + . The peak at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 461.36 eV was assigned to Ru 0 .…”
Section: Resultsmentioning
confidence: 99%